Implementation of Client-Entrusted Payment of the Duty on the Acquisition of Land and Building Rights to Land Deed Officials - Nadia Natashya Amarilis; Djumikasih; R. Imam Rahmat Sjafi’i (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study aims to analyze the practice of depositing and paying the Duty on the Acquisition of Land and Building Rights by clients to Land Deed Officials, to examine the legal basis of the officials’ authority, and to assess the forms of legal liability that arise therefrom. This research employs an empirical juridical method with statutory and conceptual approaches, supported by primary data obtained through field research in Malang City and secondary data derived from primary and secondary legal materials. The results indicate that the practice of fund deposit occurs factually as a form of transactional efficiency; however, it lacks an explicit legal basis in statutory regulations. This condition creates a normative gap that potentially leads to misuse of funds and ambiguity in legal accountability. The novelty of this study lies in affirming a legal construction that such practice is not merely an administrative issue, but also carries multidimensional implications in civil, administrative, and criminal law domains. Furthermore, this study offers an argument for the necessity of reconstructing legal norms that explicitly regulate third-party deposit mechanisms. Therefore, comprehensive regulation is required to ensure legal certainty, protect the parties involved, and maintain the integrity of Land Deed Officials within the land law and taxation system.